The PRISMA-E’xi Learning Model in Practice: Insights from a Limited Trial in Senior High School Physics Learning - Diani, Rahma; Viyanti, Viyanti; Jalmo, Tri; Lengkana, Dewi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The PRISMA-E’xi learning model integrates multiple-representation approaches, the engineering design process (STEM), and strategies designed to enhance students’ creative problem-solving skills. This study aimed to evaluate the model’s practicality through an initial implementation in senior high school physics instruction. A quantitative descriptive design was employed at the developmental research limited-trial stage, involving one tenth-grade class at SMA Gajah Mada Bandar Lampung across six instructional sessions. Data were collected through validated observation sheets assessing model implementation, teacher performance, and student activities, as well as questionnaires measuring teacher and student responses. The findings demonstrated high practicality, with implementation scoring 91.17%, teacher performance 92.31%, and student activity 88.33%, all categorized as “Excellent.” Teacher and student responses were overwhelmingly positive, with agreement levels of 98.00% and 98.95%, respectively. Although minor technical refinements were suggested, the core structure of the model remained intact and ready for broader deployment. Overall, the results indicate that PRISMA-E’xi is highly implementable, well-received, and holds strong potential to enhance student engagement and higher-order thinking in physics learning while providing teachers with a structured framework that supports 21st-century skills development.